A Brief Overview of Corrosion Prevention and Inhibition: Past, Current and Future Technologies - Ahmad - Fauzan; Andri Cahyo Kumoro; Aprilina Purbasari; Kharis Yohan Abidin (Reaktor, 2025)
Corrosion is a process that degrades metal-based materials as a result of chemical reactions with their surrounding environment. For that reason, it causes serious problems across various industries, namely reduced material quality, increased maintenance costs, and extensive safety concerns. This paper presents a concise overview of corrosion prevention and inhibition methods, focusing on key strategies, such as material selection and the use of protective coatings, cathodic protection, and corrosion inhibitors. Furthermore, nano coatings, eco-friendly inhibitors, smart materials, corrosion modelling, and self-healing materials are also discussed as part of current advancements. In-depth understanding and appropriate implementation of these suggested methods are essential for extending material lifespan and improving operational efficiency of the overall industrial systems.